THE USE OF CONTEXTUAL TEACHING LEARNING (CTL)METHOD TO IMPROVE STUDENTS’ SPEAKING MASTERY AT THE GRADE XI SMK NEGERI 1 PADANGSIDIMPUAN - Happy Sri Rezeki Purba (Linguistik : Jurnal Bahasa dan Sastra, 2016)
The researcher interviewed teacher of English about speaking mastery of students at the grade XI administration and teacher of English divide to into three category low quality were S and N, middle quality were DP and R and high quality were NN and NHL.After that the researcher observation six students to know their speaking mastery, the researcher gave some questions in English but students with low ability could not answered and just smile, then, students with middle ability could responded however combine English and Indonesian language and the last students with high ability could responded with English language.The researcher helped students to improve their speaking mastery using Contextual Teaching Learning (CTL) Method and used Cinderella text to know the result of this method especially about their pronunciation, grammar, intonation and vocabulary.